Acquired platelet disorders - Altahan, Rahaf Mahmoud (Frontiers in Medicine, 2025)
Platelets are essential to primary hemostasis, and defects in their number or function can lead to clinically significant bleeding or thrombosis. Acquired platelet disorders are far more common than the inherited forms and arise in a wide range of settings, including drug exposure, autoimmune, systemic, and critical illnesses. This review examines current understanding of the mechanisms driving acquired platelet dysfunction and outlines the diagnostic and therapeutic approaches that are shaping contemporary standards of care. Drug-related and immune-mediated platelet defects remain the most recognized causes in clinical practice. Nevertheless, increasing evidence points to inflammation, particularly the profound dysregulation seen in sepsis, as a major contributor to abnormal platelet behavior. Although sepsis-associated platelet defects are frequent in practice and correlate with organ injury and adverse outcomes, they are rarely acknowledged in traditional frameworks of “acquired platelet disorders,” which tend to focus on classic hematologic and pharmacologic causes. This review summarizes current evidence on acquired platelet disorders and emphasizes the clinical and pathophysiologic relevance of sepsis-induced platelet dysfunction.